Integrated Science Process Skills of Science, Technology and Engineering Students: Challenges and Opportunities for Improvement - Ignacio, Jengil Dimacali; Yabut, Josephine David (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2025)
The Philippines has one of the lowest average scientific proficiency scores among the PISA-participating countries and economies. The present study investigates the integrated science process skills of grade 9 Science, Technology, and Engineering (STE) program students in Angeles City, Philippines. 79 grade 9 STE program students were invited to be part of the study. They were mostly female and came from non-special science elementary schools. This study utilised a 30-item integrated science process skills test by Kazeni (2005). The reliability of the instrument is 0.81. This study used statistical analysis, specifically descriptive statistics (frequency, mean, standard deviation, one-way ANOVA, and point-biserial correlation). Based on the results, there is no significant relationship between their score from the 30-point integrated science process skills test and their gender and previous elementary school, whether the students came from special science elementary school or non-special science elementary school. This investigation recommends integrating science process skills throughout the curriculum by embedding inquiry-based learning opportunities. Courses could be designed to progress from basic science process skills such as observing, measuring, communicating, classifying, and predicting to more complex tasks such as defining operationally, formulating hypotheses, interpreting data, experimenting, and formulating models. Aligning the curriculum with frameworks that emphasise critical thinking and problem-solving, which are core components of integrated science process skills, is suggested. A series of instructional strategies that foster active student engagement with these skills, such as case- and project-based learning strategies, are proposed. The use of formative assessments is recommended to track the science process skills over time. Integration of technology tools that design and simulate experiments to offer additional avenues for skill development is encouraged.